Mixed-methods gender analysis country report, Ghana: Building equitable climate resilient African bean and insect sectors - Acheampong, Patricia; Yeboah, Stephen; Fening, Kennedy Okwae; Asibuo, James; Lutomia, Cosmas; Ouya, Frederick; Ketema, Dessalegn; Nchanji, Eileen (2025)
Agriculture remains a crucial sector for food security, economic development, and climate resilience in Africa. However, climate change-induced challenges such as unpredictable weather patterns, prolonged droughts, declining soil fertility, and limited access to climate-smart agricultural (CSA) technologies continue to hinder smallholder farmers' productivity, particularly women and youth. These groups face restricted access to financial resources, limited market linkages, and inadequate technical support, hindering their adoption of innovative and sustainable farming practices in key agricultural sectors, such as beans, fruit trees, and insect farming. This study examines the challenges and opportunities faced by men, women and youth farmers in Ghana’s bean/ cowpea, fruit tree, and insect value chains, focusing on their access to resources, training needs, and market engagement. Using mixed methods approaches to collect data from six communities across the Ashanti and Bono East regions. The findings reveal significant gender and age disparities in land ownership, group memberships, f inancial access, agricultural training, and decision-making power. Key barriers affecting women and youth farmers include limited access to quality seeds, inadequate agronomic training, poor post-harvest handling, and restricted market access. Gender-specific challenges also emerged, with women having less control over land and income, while youth struggle with credit constraints and limited agricultural extension services. Across the three value chains of beans/cowpeas, fruit trees, and beneficial insects, clear gender gaps persist in resource access, decision-making, and market participation. Women play central roles in labour-intensive stages of bean and cowpea production, including planting, harvesting, and processing, yet men control land preparation, input use, storage, and nearly all major production decisions, reflecting wider disparities such as men cultivating larger areas (8.14 vs. 5.74 acres) and women’s limited access to credit, with only 1% of farmers reporting high confidence in obtaining loans. In fruit tree enterprises, men dominate ownership, marketing, and income control, earning almost double women’s income from fruit sales and deciding on 77% of marketing actions, while women remain concentrated in lower-value local markets. The insect for food and feed sector shows similarly constrained participation for women and youth, who face limited technical knowledge, start-up capital, and extension support; men more often manage colony establishment while women engage in harvesting and processing. Overall, these findings highlight structural gender inequalities that restrict women’s productivity and benefits across all three value chains. Despite these challenges, the study identified opportunities for intervention, including training on sustainable pest management, financial literacy programs, improved storage infrastructure, and enhanced market access. The study identified high-priority training needs such as seed production, insect pest and disease management, alongside moderate-demand areas like financial literacy, record-keeping, and post-harvest management. Gender roles in agricultural value chains indicate that men dominate land preparation and input application, while women and youth play key roles in planting, harvesting, and marketing. To address these issues, the study recommends targeted interventions, including gender-responsive policies, improved financial inclusion, enhanced extension services, and climate-smart agricultural training. Strengthening market linkages across common beans, fruit tree, and insect for food and feed value chains, investing in post harvest storage, and promoting women's land rights will be critical in fostering equitable and climate-resilient agricultural systems. The insights from this research will guide the Building Equitable Climate-Resilient African Bean and Insect Sectors (BRAINS) project, ensuring inclusive and sustainable agricultural development.